On the mechanism of retrovirus-induced avian lymphoid leukosis: deletion and integration of the proviruses. - Fung, Y K (1981)
There is considerable evidence that infection by avian lymphoid leukosis viruses can led to tumor development in the target organ of the host. The mechanism by which virus-induced oncogenic transformation occurs, however, is not clearly understood. As a first step toward deciphering this process, we have characterized the proviruses of the lymphoid leukosis viruses in DNAs extracted from the leukotic and metastatic tumors by using restriction enzyme digestion and filter hybridization analysis with radioactive probes specific for the infecting genome. Our results indicate (i) that lymphoid leukosis tumors are clonal in origin; (ii) that there are multiple sites in the cellular genome of the target tissue where the virus DNA can integrate and that, in the majority of the tumors, at least one such site of each tumor is adjacent to a cellular sequence related to the oncogene of MC-29 virus; and (iii) that deletions and other structural alterations in the proviral DNA may facilitate tumorigenesis.